PENGEFEKTIFAN PENGGUNAAN RUANG PENYIMPANAN SPARE PART MEKANIK PT.INDOCEMENT PLANT 3/4 - Fahmi Husaeni (Jurnal Ilmiah Teknologi Infomasi Terapan, 2020)
Indocement is a cement producing company that has been established since 1985, and already has 13 factories located in 3 areas, namely Bogor, Palimanan and Tarjun. In a factory there are several work units including production, electrical and mechanical. In the mechanical part there is a spare part storage warehouse, which is used to store spare parts for production machines. The warehouse currently used is not too large in size only 10m x 5m. The number of spare parts that are stored very much with various sizes of spare parts ranging from small to large size spare parts, storage does not seem based on the type and size so that many small spare parts are piled up and not visible because they are covered by larger sized spare parts , so it is often re-ordered for spare parts that are actually still available in the warehouse. Spending costs for purchasing spare parts becomes greater. The methodology we use is a qualitative methodology. Using the Class-based storage method or by placing material based on the same type or similar size. Implementation of the redesign of the placement of spare parts, it is expected that spare parts will be easier to find and spare parts can be used optimally, so as to reduce the cost of purchasing spare parts. Another benefit is that it will look neater and easier to clean the warehouse area at any time.